The Study of the Emergence of Modal Functions of the Verb “Residan” (to arrive) in Persian from the Perspective of Grammaticalization - Mahmood Jafari Dehaghi; Mojtaba Monshizadeh; Fahimeh Tasalibakhsh Kaseb (̒Ilm-i Zabān, 2020)
Modal functions of the verb “residan” (to arrive) and the emergence of such modal characteristics are discussed from the perspective of grammaticalization in the present study. To achieve this goal, it was necessary to make a review on former studies on the subject of modality – more specifically, grammaticalization of modality – in Persian, followed by a description of theoretical approaches toward the concepts of modality and grammaticalization. The authors gathered data from different periods of Persian language to study the diachronic changes the verb “rasidan” has faced since the early stages of Old Persian to Middle Persian, New Persian and recent usages in Modern Persian. Analysis of data showed that in some specific contexts in New Persian, the verb “residan” was grammaticalized to represent dynamic, deserving, and permissive modality after undergoing changes such as metaphorical extension. On the other hand, in recent usages in Modern Persian, “residan” has survived, through a different path, as a means to represent dynamic modality.